2017
DOI: 10.1515/jpem-2016-0359
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of insulin like growth factor-1 and IGF binding protein-3 in healthy Indian girls from Delhi and their correlation with age, pubertal status, obesity and thyroid hormonal status

Abstract: There was no significant impact of age on IGF-1 and IGFBP-3 in pre-pubertal girls. A sudden marked increase at 11 years followed by a gradual rise in growth factors till 16 years is indicative of pubertal initiation and maturation. Subclinical hypothyroidism did not influence growth factors in girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…IGF-1 is a potential suppressor for GH. In addition, diet has been implicated as a regulator of IGF-1 levels so higher calorie intake and obesity can increase the level of IGF-1 [25,26]. Hyperinsulinemia, as a result of insulin resistance in central obesity, has a direct inhibitory effect on pituitary GH synthesis and release [24].…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 is a potential suppressor for GH. In addition, diet has been implicated as a regulator of IGF-1 levels so higher calorie intake and obesity can increase the level of IGF-1 [25,26]. Hyperinsulinemia, as a result of insulin resistance in central obesity, has a direct inhibitory effect on pituitary GH synthesis and release [24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the plasma IGF-1 concentration increased with the increasing age. Recently, it was reported that IGF-1 was a good marker of bone maturity in humans (Masoud et al 2009;Sinha et al 2016;Jain et al 2017;Marwaha et al 2017;Tripathi et al 2017) as the concentration of IGF-1 had a positive correlation with the cervical vertebral maturation index stages. The pattern of IGF-1 in the serum and plasma were low in early life and peaked at puberty and declined afterward.…”
Section: Plasma Hormones Metabolites and Bone Metabolism Markersmentioning
confidence: 99%
“…Data on the relationship between IGF-1 levels and weight in children are inconsistent. There are studies describing comparable [2], lower [29][30][31][32][33], or higher [3,20,[34][35][36][37][38][39][40][41] IGF-1 levels and higher IGF-2 levels [4] in obese children compared to their normal-weight peers. However, IGF-1 shows a tendency to drop in children with extremely high BMI values [39].…”
Section: Children's Weightmentioning
confidence: 99%
“…Higher insulin and IGF-1 levels in mid-childhood are associated with earlier puberty onset [20,50]-thelarche and menarche in girls and gonadarche in boys [34,52,56]-though there are reports describing no association [57]. The level of serum IGF-1 rises until about pubertal age, reaching a peak that is up to nine times higher than in 3-month-old babies [34] at about 11-16 years for girls, depending on the origin [29], with the mean level being slightly higher for boys [34] and eventually starting to decline [29,34]. This supports the statement of a correlation between the IGF-1 level and the onset of puberty, which is the main inhibitor of IGF-1 quantity.…”
Section: Impact Of Igf-1 and Igf-2 On Puberty In Childrenmentioning
confidence: 99%